Simulated brain strains resulting from falls differ between concussive events of young children and adults. Issue 9 (3rd July 2020) - Koncan, David; Gilchrist, Michael; Vassilyadi, Michael; Hoshizaki, Thomas B.
Abstract: Compared to adults, it has been documented that children are at elevated risk for concussion, repeated concussions, and experience longer recovery times. What is unknown, is whether the developing brain may be injured at differing strain levels. This study examined peak and cumulative brain strain from 20 cases of concussion in both young children and adults using physical reconstructions and finite element modelling of the brain response to impacts. The child group showed lower impact kinematics as well as strain metrics. Results suggest children may suffer concussive injuries with lower brain strains compared to adults.